PERTANGGUNG JAWABAN KAPAL CALEDONIAN SKY ATAS KERUSAKAN TERUMBU KARANG YANG BERADA DI RAJA AMPAT - Tasia Masyitah Purba; Abdul Rahman; Arif Arif (Journal of USU International Law, 2018)
THE CALEDONIAN SKY SHIP’S  RESPONSIBILITY FOR CORAL REEFS DAMAGE THAT WAS IN RAJA AMPAT Abdul Rahman*) Arif**) Tasia Masyitah Purba***) The sea has special properties for human life.The sea which is the breadth of water that extends between the various continents and islands in the world of function sea can be divided as a source of food for humanity, as a trade highway, as a means of conquest, as a place of battle, as a place for fun and recreation and as a means of dividing and unifying the nation.The sea makes a big contribution as a place of fun and recreation for the community, considering the natural wealth in the Indonesian sea is very diverse.Indonesia has other marine and coastal potentials that are rich in Indonesia , which are an archipelagic country , which has 17,508 groups of islands and coastal systems having various biological resources such as mangrove forests, coral reefs,Coral reef ecosystems play a role as habitat for foraging, nursery and growing up, as well as a place for spawning for marine biota. One of Indonesia's underwater wealth is coral reefs .According to the Indonesian Institute of Sciences states that coral reefs can only live in clear and shallow sea waters (less than 40 meters), with sea water temperatures of 25-28 ° c , this environment depicting tropical waters of Indonesia with its tropical climate is a very good ecosystem for coral reef growth .Lately the problem of marine pollution has become a serious concern for both national and international countries.This problem is caused by nature and also humans.And this problem is a major threat to Indonesia's coral reef damage. The writing methodusedisdescriptive method with normative juridical approach (normative legal research).intended to obtain a complete and clear picture of the problems contained in the community that are related in accordance with the legal provisions andthe applicable regulations.normative juridical approach used in this writing is writing about legal norms contained in the legislation in force and also to trace legal norms contained in the applicable dispute resolution regulations and to obtain data and informationcontained in various literature in libraries, journals, research results, internet sites, newspapers and so on. on the 4th of March 2017 the British ship MV Caledonian S who had a weight of 4,700 GT brought 102 tourists and 79 crew members and was captain of Captain Keith Michael Taylor crashing and running aground in the waters of King Ampat and causing great damage to the coral reefs in these waters .It is known that the captain of the ship refers to instructions on the GPS without considering the wave factor and other natural conditions.And therefore Indonesia seeks to hold the Caledonian Sky ship accountable for damage caused. Key word: Accountability, coral reef, the ship Caledonian Sky.   * Student of Faculty of Law University of North Sumatera **1 Thesis Adviser of Law University of North Sumatera ***2 Thesis Adviser of Law University of North Sumatera